The Implementation of Pedagogical Content Knowledge (PCK) based Guided Inquiry on Science Teacher Students - Biru, Lulu Tunjung; Prasetyaningsih, Prasetyaningsih; Vitasari, Mudmainah; Resti, Vica Dian Aprelia; Suryani, Dwi Indah (Jurnal Penelitian dan Pembelajaran IPA, 2018)
The aim of this study is examining the learning of Integrated Sciences through PCK based guided inquiry on prospective science teacher students. This research method was descriptive qualitative involving 33 science teacher students who taking Integrated Science 1 Subject in academic year 2016/2017. The research instrument used was the observation sheet to know the implementation PCK based guided inquiry. The results showed that the implementation of the activities of lecturer and science teacher students during the learning process using PCK based guided inquiry was very good conducted.